2011
DOI: 10.1364/oe.19.001656
|View full text |Cite
|
Sign up to set email alerts
|

High resolution interrogation of tilted fiber grating SPR sensors from polarization properties measurement

Abstract: The generation of surface plasmon resonances (SPRs) in gold-coated weakly tilted fiber Bragg gratings (TFBGs) strongly depends on the state of polarization of the core guided light. Recently, it was demonstrated that rotating the linear state of polarization of the guided light by 90° with respect to the grating tilt allows to turn the SPR on and off. In this work, we measure the Jones matrix associated to the TFBG transmission properties in order to be able to analyze different polarization-related parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
114
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 13 publications
5
114
0
Order By: Relevance
“…An unambiguous SPR signature appears in the TFBG amplitude spectrum, as reported in [11,12]. It is strongly sensitive to surrounding refractive index (SRI) changes [12][13][14][15], which yields an implementation of SPRbased (bio-)sensors easy to fabricate and to use.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…An unambiguous SPR signature appears in the TFBG amplitude spectrum, as reported in [11,12]. It is strongly sensitive to surrounding refractive index (SRI) changes [12][13][14][15], which yields an implementation of SPRbased (bio-)sensors easy to fabricate and to use.…”
Section: Introductionmentioning
confidence: 86%
“…It was also demonstrated recently that the differential behavior between two orthogonally polarized TFBG transmitted spectra can be used for demodulation purposes. We showed that narrowband resonant features (also located at wavelengths just below the SPR center) present a wavelength shift that enables refractive index measurements with a resolution better than 10 -5 RIU, achieved through a quality factor of 10 5 and signal-tonoise ratio greater than 50 dB [13,14]. This particular finding was supported by a recent theoretical analysis that showed how the presence of the gold layer shields azimuthally polarized cladding modes from the outside environment while allowing radially polarized ones to tunnel through and excite Plasmons [15].…”
Section: Gold-coated Tfbgsmentioning
confidence: 93%
See 1 more Smart Citation
“…The most important advantages of this biosensor platform are that it is able to provide biosensing with unique features of label-free, real-time, multiplex, and in-line determination. Various fiber optic biosensors have been presented by employing long period gratings (LPGs) [7,8], tilted fiber gratings (TFGs) [9][10][11] micro fiber Bragg gratings (mFBGs) [12] LPGs in photonic crystal fibers [13] and surface plasmon resonance (SPR) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the other types are complex, and hence they have not been widely used, although their ability to offer higher sensitivities has been demonstrated [8,9]. Recently, in order to improve the sensitivity and practicality of SPR sensors and extend their applications, many research works have been focused on devising new configurations and mechanisms while retaining the simplicity of conventional SPR sensors [10,11]. Among them, plasmonic cavities have generally been used to enhance the sensitivity of the SPR sensors [12,13].…”
mentioning
confidence: 99%